PENGARUH INTERNETADDICTION TERHADAP MOTIVASI BELAJAR SISWA UPTD SMP NEGERI 2 PEMATANGSIANTAR SEMESTER GENAP TAHUN AJARAN 2023-2024 - Grace Veronika Parapat; Binsar Tison Gultom; Anton Luvi Siahaan (JOURNAL SAINS STUDENT RESEARCH, 2024)
This study aims to determine: (i) the internet use of class VIII at UPTD SMP NEGERI 2 Pematangsiantar (ii) the level of learning motivation of students in class VIII at UPTD SMP NEGERI 2 Pematangsiantar (iii) how much influence internet addiction has on student motivation in class VIII at UPTD SMP NEGERI 2 Pematangsiantar. The method used is a survey method with a quantitative approach by distributing questionnaires for data collection. The results of the research show: (i) internet addiction to students is said to be good with an average value of 3.50, which means students answer disagree with negative statements (ii) the level of student motivation is said to be good with an average value of 3.80(iii) there is an effect of internet addiction on students' learning motivation by 20.3%. Suggestions submitted by researchers to: (i) students, are expected to be able to use the internet properly and wisely so that it can be used as a source for learning and it is hoped that with the internet students can increase their learning motivation (ii) teachers, are expected to pay more attention to students in using the internet so that they are not abused and motivate students to be more active in learning (iii) further researchers are expected to be used as reference material in the future in the hope of developing deeper so that they get better results again.